ECOGEOPHYSICS INVESTIGATIONS OF TECHNOGENIC POLLUTION IN ZONE OF MINERAL MANURE REPOSITORY - ONYSHCHUK, V.; REVA, M.; ONYSHCHUK, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The feathers of geophysical prospection methods for studying of geological environment technogenic pollution are shown. The geoelectrical parameters of various types of rocks of profile’s upper part are revealed with regarding of pollution intensity.